The Ambiguities of Iconic Design: Mo Modern Art Museum by Daniel Libeskind - Samalavičius Almantas (Journal of Architectural Design and Urbanism, 2019)
The article is focused on the cultural phenomena of architectural iconism that has become globally widespread due to the continuous pressure of ongoing economic, ideological and cultural globalisation and the reigning interests of the web of building industry that appropriates architectural design for its own financial purposes as well as local political stakeholders who often seek to replicate the success of previous internationally renowned iconic buildings by aspiring to the status of world-class cities. While discussing the global and local cultural contexts in which the so-called ‘Bilbao effect’ triggered the current pursuit of iconic buildings, the author of the article analyses the much publicized recent example of iconic architecture in Eastern Europe – the MO Modern Art Museum that was designed by Daniel Libeskind and opened in Vilnius, the capital of Lithuania in 2018 on the site of an abandoned and eventually demolished cinema in the vicinity of the historical Old Quarters. It is argued that despite of publicity and largely overcooked praises of international architectural media, the museum’s architectural design remains an example of ‘signatory architecture’ that largely ignores the aesthetics of its local urban environment and peculiarities of local historical and cultural context. It is suggested that that despite of claims of being contextual, in fact the building is not and on the contrary: it exhibits most of the aesthetics features that plaque iconic buildings in various localities on different continents.